2019
DOI: 10.3389/fonc.2019.00423
|View full text |Cite
|
Sign up to set email alerts
|

The Role of 5-ALA in Low-Grade Gliomas and the Influence of Antiepileptic Drugs on Intraoperative Fluorescence

Abstract: Objectives: Intraoperative tumor visualization with 5-aminolevulinic acid (5-ALA) induced protoporphyrin IX (PpIX) fluorescence is widely applied for improved resection of high-grade gliomas. However, visible fluorescence is present only in a minority of low-grade gliomas (LGGs) according to current literature. Nowadays, antiepileptic drugs (AEDs) are frequently administered to LGG patients prior to surgery. A recent in-vitro study demonstrated that AEDs result in significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 43 publications
3
35
1
2
Order By: Relevance
“…In a study by Valdes et al in which 5-ALA was evaluated in 12 cases of LGG, including two gangliogliomas, faint visual and quantitative probe-based fluorescence could only be detected in one of the two [ 14 ]. In another series with 27 LGG, including one desmoplastic infantile ganglioglioma, moderate diffuse fluorescence was reported by Goryaynov et al, using a slightly higher 5-ALA dose (25 mg/kg) [ 15 ]. Another retrospective study by Preuss et al evaluating 5-ALA in 18 pediatric patients with suspected brain tumors found minimal positive staining of the internal parts of the tumor but no enhancement of the tumor in one of three gangliogliomas [ 13 ].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In a study by Valdes et al in which 5-ALA was evaluated in 12 cases of LGG, including two gangliogliomas, faint visual and quantitative probe-based fluorescence could only be detected in one of the two [ 14 ]. In another series with 27 LGG, including one desmoplastic infantile ganglioglioma, moderate diffuse fluorescence was reported by Goryaynov et al, using a slightly higher 5-ALA dose (25 mg/kg) [ 15 ]. Another retrospective study by Preuss et al evaluating 5-ALA in 18 pediatric patients with suspected brain tumors found minimal positive staining of the internal parts of the tumor but no enhancement of the tumor in one of three gangliogliomas [ 13 ].…”
Section: Discussionmentioning
confidence: 95%
“…Apart from standard microsurgical resection utilizing the operating microscope, 5-aminolevulinic acid (5-ALA) fluorescence has been evaluated as an intraoperative tool for improved visualization with limited to no benefit [ 13 , 14 , 15 ]. Near-infrared optical imaging in one study could visualize tumors with preoperative gadolinium enhancement on MRI [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…So far, it is hard to elucidate which mechanism is most determinate of 5-ALA accumulation. Observed foci of fluorescence in low-grade gliomas were correlated with anaplastic transformation and increased cellularity (216,217), which in turn may result in a less competent BBTB that is permeable to 5-ALA but not to gadolinium-based contrast.…”
Section: -Ala Delivery Across the Bbtbmentioning
confidence: 99%
“…PSs have been utilized for their fluorescence for decades since the pioneering works of R. L. Lipson and S. Schwartz in the 1960s [25,26,185,186]. The most impactful use of Photosensitizer Fluorescence Detection (PFD) to date has been for image-guided resection of brain and bladder cancers [187][188][189][190][191], which are now approved by regulatory authorities worldwide. These approvals were based on clinical trials using ALA-PpIX (5-aminolevulinic acid induced protoporphyrin IX conversion) based PFD for guiding resection, which demonstrated a significant increase in tumor-free survival as compared to white-light based tumor resection surgery (Figs 7a-7d) [187,192,193].…”
Section: Optical Imaging For Diagnostics and Therapy Guidance In Pdt mentioning
confidence: 99%
“…Images in (c) and (d) were acquired by neurosurgical microscope equipped with a fluorescent 400 nm UV light module. Figures adapted from Zaak et al (2005)[191] and Goraynov et al (2019)[190].…”
mentioning
confidence: 99%